2022
DOI: 10.1177/00812463221086379
|View full text |Cite
|
Sign up to set email alerts
|

Police interventions in victims’ encounters of intimate partner violence in a rural setting

Abstract: One of the most frequently experienced types of violent crime in South African rural communities is interpersonal violence, which includes intimate partner violence. Rural policing is among the vital forms of intervention required to manage such incidents. This article employs a qualitative interpretative phenomenological analysis approach, to describe and interpret police members’ experiences of policing victims’ encounters of intimate partner violence in the rural Vhembe district in Limpopo. Fifteen police m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…Police were found to not take the participants’ plight seriously. This is congruent with the study of (Yesufu 2022 :97), who identified police as lacking the capacity and sensitivity required to address IPV matters, and that makes victims feel responsible or at fault, thus contributing to secondary victimisation (Gouws 2022 :2; Gumani 2022 :380).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Police were found to not take the participants’ plight seriously. This is congruent with the study of (Yesufu 2022 :97), who identified police as lacking the capacity and sensitivity required to address IPV matters, and that makes victims feel responsible or at fault, thus contributing to secondary victimisation (Gouws 2022 :2; Gumani 2022 :380).…”
Section: Discussionsupporting
confidence: 84%
“…Church leaders were seen as lacking knowledge on the prevention of abuse and not offering any effective support as this would contradict their inherent support for patriarchy. Furthermore, police officers were viewed as being biased and often blamed IPV survivors for instigating the violence they had experienced (Gumani 2022 :380).…”
Section: Resultsmentioning
confidence: 99%